Interview transcript with Puan Rahimah binti Othman, Alumni of Faculty Library Science about her experience and career being an alumni from Library Science in Institut Teknologi MARA (ITM) - Spiee, Noor Azwa; Abdul Hamid, Siti Nurulhuda (Fakulti Pengurusan Maklumat, 2020)
This transcript discuss about the experiences or contributions of a figure, Puan Rahimah Othman who is an alumni from Library Science at Institut Teknologi MARA (ITM) in 1976. There are a lot differences between then and now about the learning session in Library Science. In this oral history also tells a lot of the figure's experience during the study period and the figure also give some good advises for the student of Faculty Information Management nowadays to do their best in every field. The experiences that the figure has been told, give the student a lot of knowledge about the content of Library Science then and now. It's will give students nowadays a bit of awareness and enthusiasm towards what they are going through now. From this oral history also, the student nowadays can get a little bit information about the history of development of Institut Teknologi MARA (ITM) and the background of the Library Science Faculty. This research are focusing on the background of the figure and her career experiences, the details about the Library Science such as definition or responsibilities, and the courses or co-curriculum that offered in Library Science at that time. Beside that, it is also covers about the teaching and learning session procedure in the faculty during that time. Moreover, it is also tell about the details of library in Institut Teknologi MARA (ITM) and in Malaysia. From this oral history documentation, the students nowadays can get a lot of knowledge about library or archives and get to know the history of Institut Teknologi MARA (ITM) and Library Science Faculty.